Paper Distribution Route Optimization Using Ant Colony Method at PT. XY - Nezarulloh, Muhammad Yusril; Sumiati, Sumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
In distributing their products, companies need to determine distribution routes to optimize the distanceof distribution process and minimize losses, such as distribution by PT. XY is carried out randomly without regard to the location betweenthe customers to be addressed, so that the distance and time taken is excessive resulting in a lot of costs to be incurred. Therefore, planning needs to be done to optimize the distance and time of distribution. The purpose of this study was to determine the paper distribution routes at PT. XY so that the distance and travel time traveled are much more optimal by using the Ant Colony Optimization method. Based on research, the distribution of PT. XY using the Ant Colony Optimization method obtained more optimal results than using the company's initial route design. The total route distance was originally 423.4 km to 310.4 km, and the original total time was 695 minutes to 554 minutes. So it was concluded that there was a total route distance saving of 113 km and a distribution time of 141 minutes. Thus, in the distribution process at PT. XY with the application of this method can minimize costs that must be incurred by the company.